The Many-Sidedness of George Minchin Minchin Educator, Satirist, and Early Pioneer of Television - Hornsey, Richard (Cham : Springer International Publishing : Imprint: Springer, 2023)
This book is the first complete biography of George Minchin Minchin (1845-1914), professor of applied mathematics at the Royal Indian Engineering College. Minchin's extraordinary range of accomplishments offers a unique inside view of the major technological and educational developments of late nineteenth century Britain. The scientific community's excitement during the early days of electromagnetic theory, wireless telegraphy, and x-rays are revealed by Minchin's letters to eminent friends (notably the Maxwellians, Oliver Lodge and George Francis Fitzgerald). This book also traces Minchin's little-known pioneering work on photoelectricity, which led to the first electrical measurements of starlight and laid the foundations for solar cells and television. Minchin's mathematical textbooks were praised for their lucidity, and his advanced pedagogical thinking underpinned his lifelong work on reforming science education. He explained scientific concepts for a general audience using science fiction poetry and critiqued contemporary society in sharp and humorous satires. These works provide fresh perspectives on the place of science in Victorian society. This book is for anyone fascinated by the late nineteenth century revolution in electrical technologies.This is also a valuable read for historians of science, and for those interested in technical education, and science and society in Victorian Britain.
Chapter 1. Eminent in the World: introduction and motivation -- Chapter 2. Minchin Minchin: Early Years And University in Ireland -- Chapter 3. Is the Monkey Smooth? A Career at Coopers Hill -- Chapter 4. An Honorary Maxwellian: Colleagues and Electromagnetic Theory -- Chapter 5. Ne Plus Ultra: Textbooks and Writing -- Chapter 6. Geometry Versus Euclid: Reforming the Teaching of Mathematics -- Chapter 7. Journeys to Al Fard and Other Exotic Destinations: Satires and Poems -- Chapter 8. Telephotographs: Photocells and Photo-batteries, 1880 - 1891 -- Chapter 9. Distant Scintillating Star: Starlight, X-rays, and Television, 1891 - 1908 -- Chapter 10. Balak, the Son of Zippor: Impulsion Cells and Wireless Telegraphy -- Chapter 11. Through Nature to eternity Final Years and Reflections.
Keywords: Intellectual life -- History; Science -- History; History; History of Ideas; History of Science; History